Evaluación de las variables del comportamiento organizacional mediante el empleo de indicadores de gestión en comisariato Cleymer del cantón Bolívar. - Bravo Bravo, Tito Valentín (2018)
To evaluate the variables of the organizational behavior of the Cleymer commissary located in Bolívar canton, it was required the establishment of 3 phases, in the first one, the organizational behavior variables that are opportune through a group of experts are established, the coefficient of competence was identified, guaranteeing the viability in the selection; in phase 2, the evaluation tool (questionnaire) was structured (Bravo, 2017), where the management indicators are established, the questions contained in each variable of the individual, group and organizational level are structured, to later apply it to each employee of the organization; the results obtained are tabulated using the Microsoft Excel program, where the average value of the questions and variables is established (overall result), making the inductive-deductive and analytical-synthetic methodology indispensable at this stage; followed by this, the third phase, the critical analysis was developed, where the areas to be reformed were determined and an improvement plan was proposed that defined the corrective and preventive actions according to the results obtained, applying the matrix tool 5w + 1h. The process described above allows us to define the study: the level of the Organizational Behavior of Cleymer commissary, presents good performance in terms of motivation and teamwork variable; however, its operations can be affected by the lack of strategic planning and adequate official communication channels, contributing to the communication and organizational culture variables, which are close to falling to deficient levels.